Prevalence of gymnastics-based movement abiblity/inability amonghigh-intensity functional training practitioners - Kilipper, Rafael; Okuyama, Alexandre Ricardo; Antonio Joaquim, Victor Hugo; Rebouças Cunha, Adriano Patrik; Alves Oliveira, Alinne; Pereira, Rafael (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Gymnastics-based exercises comprise complex movements used in many high-intensity functional training (HIFT) workouts, but the prevalence of ability/inability to perform these exercises is unknown. Aim of Study. This study investigated the rate of practitioners able/unable to perform each gymnastics-based movement applied in HIFT workouts. Material and Methods. Using a “virtual snowball” sampling method 1325 volunteers (women: 738; men: 587) answered an online survey. The rates for the ability/inability were estimated for the following movements: pull-up (PU) and its variations (strict pull-up [SPU], kipping/butterfly PU, strict chest-to-bar [SCtB], kipping/butterfly CtB), strict (STtB) and kipping toes-to-bar (TtB), bar muscle- -up (BMU), ring muscle-up (RMU), handstand hold, handstand push-up (HSPU) and handstand walk (HSW). The rates were also stratified according to sex. Results. Our results demonstrated a high rate of inability in strict movements: SPU, SCtB, STtB, strict HSPU, strict BMU, strict RMU, and handstand hold, especially among women. The use of the kipping technique allowed one to perform many of these movements, since the prevalence of inability was lower for kipping movements than for strict ones. The exception was the kipping PU, since among men the percentage of volunteers unable to perform kipping/butterfly PU was slightly greater than SPU, suggesting a deficiency in the technical aspects of this movement. Additionally, kipping BMU, RMU, and HSW were the “dynamic” movements (i.e. excluding the strict ones) with greater rates of inability (≥50%), suggesting the need for more attention by coaches. Conclusions. Our results allow reflecting upon coaches’ approaches to teaching complex gymnastics-based exercises to persons without a gymnastic background, as well as reflecting upon further research to develop an understanding of interventions used to improve gymnastics-based exercises, transferring the key research findings into practice.
Keywords: muscle strength; gymnastics; mixed modality; training; calisthenics